Determinan Keputusan Nasabah dalam Memilih Produk Tabungan Easy Wadiah pada Bank Syariah Indonesia - Wafia Multazima; Ika Khusnia Anggraini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze service quality, consumer knowledge, religiosity and location on customer decisions in choosing Wadiah Bank Syariah Indonesia savings products in East Java Province. This research uses quantitative methods with SEM-PLS analysis. The data collection method is through distributing questionnaires, which are measured using a Likert Scale. The population in this research is people who have easy wadiah savings in East Java Province. The research results show that the variables of service quality, consumer knowledge and religion have a significant positive effect on consumer decisions, while the location variable does not have a significant effect on consumer decisions